2021
DOI: 10.1038/s41366-021-00762-0
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient intake during pregnancy in women with a history of obesity or gestational diabetes and offspring adiposity at 5 years of age

Abstract: Background/objectives The impact of maternal macronutrient intake during pregnancy on offspring childhood adiposity is unclear. We assessed the associations between maternal macronutrient intake during and after pregnancy with offspring adiposity at 5 years of age. Additionally, we investigated whether gestational diabetes (GDM), BMI, or breastfeeding modified these associations. Subjects/methods Altogether, 301 mother–child dyads with maternal prepregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Potential adverse results on offspring outcomes related to fat intake of GDM mothers may be associated with the quality of fat, i.e. the proportion of saturated fatty acids (SFA) in the diet instead of the total amount of fat (52). Fetal exposure to higher circulating levels of free fatty acids has been found to be associated with the increased risk of proportionally higher adiposity of the offspring of GDM women (20-22, 50, 52).…”
Section: Discussionmentioning
confidence: 99%
“…Potential adverse results on offspring outcomes related to fat intake of GDM mothers may be associated with the quality of fat, i.e. the proportion of saturated fatty acids (SFA) in the diet instead of the total amount of fat (52). Fetal exposure to higher circulating levels of free fatty acids has been found to be associated with the increased risk of proportionally higher adiposity of the offspring of GDM women (20-22, 50, 52).…”
Section: Discussionmentioning
confidence: 99%
“…In our study pregnancies leading to adverse offspring growth showed lower mean levels of several unsaturated fatty acids in the 3rd trimester. Fatty acids are strongly correlated with dietary intake and interestingly we have previously shown that maternal dietary n-3 PUFA intake during pregnancy was associated with offspring adiposity at 5 years of age [ 43 ]. This has been investigated also in a RCT, where omega-3 supplementation for women with obesity improved fetal growth in lean mass and longer gestation [ 44 ].…”
Section: Discussionmentioning
confidence: 99%